Case Studies to illustrate the Rotorcraft Certification by Simulation Process; CS 29/27 Low-Speed Controllability - Hoff, S. van 't; White, M.; Dadswell, C.; Lu, L.; Padfield, G.; Quaranta, G.; Podzus, P. (My University, 2023)
This paper is one of a set presented at the 49th European Rotorcraft Forum discussing results from the EU Clean Sky 2 project, Rotorcraft Certification by Simulation (RoCS). The process developed by the RoCS team provides guidance on the use of flight simulation in certification and features four case studies that illustrate aspects of the process using flight simulation models and flight test data provided by Leonardo Helicopters. This paper presents the case study for the low-speed controllability requirements from the relevant certification paragraphs in the EASA Certification Specifications CS-27 and CS-29. Following an introduction of the related specifications, and the motivation behind seeking compliance supported by simulation, the various phases of the RCbS process are explored in more detail. The intent is to exercise aspects of the RoCS guidance in a practical application to investigate the implementation, and the strengths and limitations, given real-world con-straints. Emphasis is placed on the Validation & Verification as well as the Credibility Assessment, taking into account test and simulation uncertainties. Results from piloted simulation trials are included to illustrate possi-ble flight simulator fidelity assessment methods.
Keywords: Certification by Simulation